(untitled) (Tanzania Medical Journal, 2025)
Background: Biliary obstruction carries high morbidity and mortality, often complicated by diagnostic challenges. While Magnetic Resonance Cholangiopancreatography (MRCP) offers a noninvasive method for detecting biliary strictures, its accuracy compared to the established Percutaneous Transhepatic Cholangiopancreatography (PTC) remains underexplored in Tanzania. This study evaluates the diagnostic performance of MRCP against PTC among patients with obstructive jaundice at Muhimbili National Hospital (MNH), aiming to support evidence-based clinical decision-making. Objective: To determine the diagnostic accuracy of MRCP compared to PTC for detecting biliary strictures in patients with obstructive jaundice treated at MNH from July 2019 to December 2022. Methodology: This cross-sectional study was conducted at MNH from July 2019 to December 2022. Patients with obstructive jaundice who underwent both MRCP and PTC were selected using non-probability consecutive sampling. The study assessed the sensitivity, specificity, negative predictive value (NPV), positive predictive value (PPV), and overall accuracy of MRCP compared to PTC results. Results: In a study of 57 obstructive jaundice patients, MRCP demonstrated high performance in identifying ductal strictures, with sensitivities ranging from 70.0% to 98.1% and specificities between 89.4% and 100%, depending on the stricture site. PPV varied from 58.3% to 100%, while NPV ranged from 75.0% to 95.6%. The overall diagnostic accuracy for MRCP across all stricture types was notably high at 98.2%. Conclusion: In the current study, MRCP has demonstrated a high overall diagnostic accuracy in the detection of biliary strictures. Therefore, affirming the reliability and consistency of MRCP as a valuable non-invasive diagnostic tool for biliary strictures. Recommendation: Physicians should utilize a non-invasive MRCP technology to ensure accurate and timely diagnosis of biliary strictures.